Enhancing water security and landscape resilience through multibenefit land repurposing - Penny, Gopal; Rodríguez-Flores, José M.; Fernandez-Bou, Angel Santiago; Koebele, Elizabeth A.; Schiller, Anna; Solomon, Divya; Carlson, Katie; Classen-Rodriguez, Leticia; Daniels, Molly; Grimm, Robyn; Hall, Maurice; Kiparsky, Michael; et al. (Frontiers in Water, 2025)
Achieving water sustainability in many water-scarce regions will require reducing consumptive water use by converting irrigated agricultural land to less water intensive uses. Conventional approaches to this challenge that emphasize water conservation as a singular objective often promote ad hoc practices that temporarily leave land idle while missing an opportunity to enhance landscape resilience and harness synergies of managing water and land together. Multibenefit land repurposing offers an alternative solution to this challenge by strategically transitioning irrigated agricultural land to other beneficial uses that consume less water and provide benefits for multiple constituencies. In practice, multibenefit land repurposing involves the process of collaboration among different groups (e.g., growers and community members) and the outcome of converting irrigated agriculture to other multibenefit uses (e.g., groundwater recharge basins with habitat and water quality benefits). It integrates into a single framework the joint objectives of conserving water, creating benefits for society and the environment, and stimulating the growth of participatory governance networks. But the pathways through which multibenefit land repurposing can achieve these objectives have yet to be demonstrated, either empirically or conceptually. To this end, we illustrate conceptually how multibenefit land repurposing can be designed to enhance water security and enable a transition to more resilient landscapes, building a theory of change around three key elements: (i) creating multibenefit outcomes, (ii) improving strategic regional coordination, and (iii) shifting underlying institutional conditions to promote innovation, adaptation, and cooperation. We draw from experience with the ongoing Multibenefit Land Repurposing Program (MLRP) in California, which has brought together over 100 different organizations in support of eight regional teams to work collectively on coordinated land transformation. We use examples from MLRP to illustrate key components and challenges of the theory of change, including how multibenefit land repurposing may be implemented in practice. Despite being a relatively new approach, we argue that multibenefit land repurposing offers a pathway to building resilient landscapes, including in regions with historically severe and inequitable depletion of water resources.